EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS DAN TEAM ASSISTED INDIVIDUALIZATION PADA MATERI GARIS DAN SUDUT DITINJAU DARI KECERDASAN EMOSIONAL SISWA KELAS VII SMP NEGERI SE-KABUPATEN MAGETAN TAHUN PELAJARAN 2013/2014 - Annurwanda, Pradipta; Mardiyana, Mardiyana; Sari S, Dewi Retno (Journal of Mathematics and Mathematics Education, 2014)
Abstract: This aim of the research was to know the effect of learning models on mathematics achievement viewed from the student emotional intelligences. The learning model compared were TGT, TAI and direct learning. The type of the research was a quasi-experimental. The population was all of student seventh grade of junior high school in Magetan regency on academic year 2013/2014. The sampling technique by using a stratified cluster random sampling. The size of the sample was 252 students with 85 students as experimental class I, 86 students as experimental class II, 81 students as control class. The data collections were taken by document, questionnaire and test method. Hypothesis testing was performed by using an unbalanced two way analysis of variance. The conclusions of Â the research were as follows: (1) TGT learning model give better mathematics achievement than TAI and direct learning model, TAI learning model give an equal mathematics achievement to direct learning model, (2) the high level emotional intelligence students have an equal mathematics achievement to the middle level emotional intelligence students, the high level emotional intelligence students have better mathematics achievement than the low level emotional intelligence students, the middle level emotional intelligence students have better mathematics achievement than the low level emotional intelligence students, (3) for the high level emotional intelligence students, TGT, TAI and direct learning models give the same mathematics achievement, for the middle level emotional intelligence students, TGT learning model give the same mathematics achievement as TAI and direct learning model, direct learning model give better mathematics achivement than TAI learning model, for the low level emotional intelligence students, TGT learning model give the same mathematics achievement as TAI learning model, TGT learning model give better mathematics achievement than direct learning model, TAI learning model give the same mathematics achievement as direct learning model, (4) on the TGT and TAI learning models, students in each level of emotional intelligence have the same mathematics achievement, for student with direct learning model, the high level emotional intelligence students have the same mathematics achievement as middle and low level emotional intelligence students, the middle level emotional intelligence students have better mathematics achievement than low level emotional intelligence students.Keywords: Teams Games Tournaments, Team Assisted Individualization, direct learning, emotional intelligence.